Cumulative ongoing pregnancy rate achieved with oocyte vitrification and cleavage stage transfer without embryo selection in a standard infertility program - F. Ubaldi; R. Anniballo; Stefania Romano; E. Baroni; L Albricci; Silvia Colamaria; Antonio Capalbo; F Sapienza; Gábor Vajta; Laura Rienzi (2010)
Recent advancement of minimum volume vitrification methods has resulted in a dramatic increase in the efficiency of the process. The aim of this study was to estimate the cumulative reproductive outcome of a cohort of infertile couples undergoing ICSI and oocyte vitrification in restrictive legal conditions, where only a limited number of oocytes could be inseminated per cycle and embryo selection and cryopreservation were forbidden. In this prospective longitudinal cohort study, the cumulative ongoing pregnancy rates obtained by the insemination of fresh and vitrified oocytes from the same cohort were calculated as primary outcome measures. Moreover, the effect of basal and cycle characteristics on clinical outcomes were assessed. Between September 2008 and May 2009, 182 ICSI cycles were performed where oocyte vitrification was possible. A total of 104 first and 11 second oocyte warming cycles were then performed in non-pregnant patients of the same cohort. The overall ongoing pregnancy rates obtained in the fresh, and first and second warming cycles were 37.4, 25.0 and 27.3%, respectively. The overall cumulative ongoing clinical pregnancy rate observed per stimulation cycle was 53.3%. Maternal age was the only characteristic found to influence the reproductive outcome, with an inverse correlation between the age >40 and the ongoing pregnancy rates (P = 0.04, by Cox regression analysis). High cumulative ongoing pregnancy rates can be obtained with transfers of embryos derived from fresh and cryopreserved oocytes in a typical infertile population. Female age significantly affects outcomes in this system.